A genre analysis of abstracts by non-native english speaking (NNES) scholars in Malaysian journals - Edward,, Ngui How Lai. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The emerging abstract genre in scholarly publication has led to the growing concern towards abstracts written by novice writers, in particular non-native English speakers (NNES). This study investigates the rhetorical structures and language features of NNES writers of English abstracts published in Malaysian journals.The text analysis on 50 abstracts in 7 local journals from the field of applied linguistics has found a considerable match with Santos’ (1996) five- move pattern and Weissberg and Buker’s (1990) verb tenses specifications despite the variations and problems identified in the corpus. The results showed that 28 out of the 50 abstracts (56.0%) included the 3 fundamental moves (i.e. purpose, methodology and results) in a logical order. Of particular variations were the two unspecified forms for the background(i.e. practical problem to lead to purpose)and purpose statements(i.e. presenting outcome/findings) and the preponderant use of present tense in presenting purpose, methodology and results instead of the past tense. The four main flaws were the omission of moves(especially the fundamental ones), loss of move status(in particular the methods, results and discussions), confusion in the order of moves and unsound evaluative claim in the present without modulations. In addition, the infrequency of extending previous research (in situating research), reporting the scope of research (in describing methodology), suggesting solutions to problems (in summarising results) and the lower tendency to draw conclusion than to give recommendations(in discussing research) were observed. This study concludes that NNES should assimilate prescribed conventions so that their writings conform to the expectation of the discourse community they are writing to and simultaneously, fulfill their different writing needs.The incorporation of findings into instructional materials should emphasise the specific writing skills and problems identified to enhance NNES’ writing of more effective abstracts.